(untitled) (Gremium, 2016)
The Tokyo Tower and the Tokyo Skytree are the two most recognizable landmarks on the skyline of Japan’s capital. By means of a documental revision, a textual interpretative analysis of media contents, participant observation and unstructured interviews, the objective of this article is to identify the development of these towers as symbols of Tokyo and Japan. It is found that, with more than half a century of existence, the Tokyo Tower represents the successful postwar Japanese society, while in just five years the Tokyo Skytree has become a symbol of Japanese national spirit and resilience in an era of multiple crises. Both broadcasting towers are regularly portrayed in Japanese media linked to narratives of romance, dreams, family and community. Also, enhanced by their special lightening at night, they stand as attractive poles for locals and visitors to choose them as background in relevant events in their lives.